Capability Management Guide Method Support for Enterprise Architectures Management - Wißotzki, Matthias (Springer Fachmedien Wiesbaden : Vieweg, 2018)
This book investigates what enterprises can do and/or what should it be capable of in order to accelerate organizational changes. Therefore, a capability-based method is developed, which assists in the identification, structuring and management of capabilities. The approach is embedded in a process comprising four building blocks that provide appropriate procedures, concepts and supporting tools evolved from theory and practical use cases. The guide represents a flexible method for capability newcomers and experienced audiences to optimize enterprises' economic impacts of EAM supporting the alignment of business and IT. Contents Enterprises and their Environments Enterprise Models and Architectures Strategic Enterprise Architecture Management Enterprise Architecture Management Capabilities Capability Management Guide Target Groups Student s in business information systems and business management studies Researchers in the field of business information systems Practitioners such as enterprise architects, digital transformation managers and tech entrepreneurs The Author Matthias Wißotzki is currently working as researcher and lecturer investigating topics like capability management, digital transformation and business model engineering at the University of Rostock.